Antigua and Barbuda : Staff Report for the 2012 Article IV Consultation, Seventh Review under the Stand-By Arrangement and Financing Assurances Review, Request for Waiver of Nonobservance of Performance Criterion and Request for Waiver of Applicability. (IMF Staff Country Reports; Country Report, 2013)
This article is a report of the IMF Executive Board's program for Antigua and Barbuda. The Stand-By Arrangement program was developed as a response to the looming fiscal crisis, which resulted in large fiscal deficits and debts similar to the global crisis. The program is approved to support fiscal adjustment, debt restructuring, reduction of arrears, and financial reforms. The program attained significant progress. The Executive Board takes this potential growth as an achievement in the global competition.